Hypereosinophilia: A Guideline for Workup in the Allergy Community (Canadian Allergy & Immunology Today, 2022)
Determining the etiology of eosinophilia, defined as an absolute eosinophil count (AEC) greater than 500 cells/µL, is often difficult given the many potential causes spanning several medical specialties. The diagnosis becomes more urgent in the case of hypereosinophilia (≥1,500 cells/µL) due to concerns over potential end organ damage. The goal of this review is to educate physicians about the biology, etiologies, and workup of hypereosinophilia.